ROLE MODEL PERLINDUNGAN HUKUM BAGI APOTEKER (Persfektif Hermeneutika Hukum) - Mulyani, Basri; Malik, Djamil Abdurrahman; Nufus, Lale Syifaun (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
Pharmacists as a health professional have a strategic role in the current era of the health industry. Not only does it relate to professional entities that have special expertise in the production, distribution and availability of health supplies. But it plays a role in the health service aspect. In the four changes to health legal regulations, this has been accompanied by a new paradigm oriented towards the best service for patients. The optics used in this research rely on hermeneutics as the basic basis for text interpretation in order to capture the meaningful sense produced through a dialectical process related to the provisions of Article 304 in conjunction with Article 310 of Law no. 17/2023 concerning Health, which in principle provides space for the parties (patients and the pharmacist profession) to resolve problems outside of court. This type of normative doctrinal research, secondary data sources are primary, secondary and tertiary legal materials using a conceptual approach and a statutory approach. The research results show that in the role model, dispute resolution between patients and pharmacists can occur if in practice the health services provided are not based on good faith so that patients who experience losses can claim compensation by first taking efforts to resolve the dispute outside of court.